2018
DOI: 10.1371/journal.pone.0201884
|View full text |Cite
|
Sign up to set email alerts
|

Studying additive interaction in a healthcare database: Case study of NSAIDs, cardiovascular profiles, and acute myocardial infarction

Abstract: PurposeThere are clinical trial data on risk of acute myocardial infarction (MI) with nonsteroidal anti-inflammatory drugs (NSAIDs) in patients at increased cardiovascular (CV) risk requiring chronic daily treatment. This study investigated whether risks of acute MI with real-world prescription NSAIDs, such as low-dose or intermittent use, vary according to an individual’s CV profile.MethodsNested case-control analyses were carried out on an administrative health cohort from Quebec, Canada by randomly selectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Similarly, it has long been recognized that additive interaction is more relevant for clinicians, public health practitioners, and policy makers because it highlights the individuals in the population who would benefit most from an intervention . Based on the interpretation of superadditive interaction from our results, the number of deaths in aging women who have high BMI is greater than the number of deaths expected from either high BMI or increasing age independently . Ultimately, whether additive or multiplicative interaction is most relevant depends on the question that the researchers are trying to answer.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, it has long been recognized that additive interaction is more relevant for clinicians, public health practitioners, and policy makers because it highlights the individuals in the population who would benefit most from an intervention . Based on the interpretation of superadditive interaction from our results, the number of deaths in aging women who have high BMI is greater than the number of deaths expected from either high BMI or increasing age independently . Ultimately, whether additive or multiplicative interaction is most relevant depends on the question that the researchers are trying to answer.…”
Section: Discussionmentioning
confidence: 74%
“…Estimates for ratios of risk ratios and 95% confidence intervals were obtained using Fieller's method incorporating predicted marginal prevalences and standard errors from SUDAAN. Interactions on the additive scale are of particular interest from a public health perspective, as they point to groups that experience the greatest population-level risk (or shifts in risk) and thus may represent important targets for prevention and intervention (see the Supplemental Material section and Table S6 in the online supplement) (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). To yield estimates representative of the U.S. adult population, we incorporated the survey weights, and used SUDAAN 11.0.1 (46) to adjust for the complex sampling designs.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Concomitant use of cardioprotective aspirin does not appear to reduce the risk of acute MI with NSAIDs. 41 A subsequent analysis using data from the Quebec administrative health cohort confirmed that all five NSAIDs, including naproxen, are associated with increased risk of MI. This increased risk exists for celecoxib after continuous use for more than 30 days, whereas, for the other four NSAIDs, it occurs within 7 days of use.…”
Section: Methodsmentioning
confidence: 96%
“…The ORs for the five NSAIDs studied were 1.24 (0.91-1.82) for celecoxib, 1.48 (1.00-2.26) for ibuprofen, 1.50 (1.06-2.04) for diclofenac, 1.53 (1.07-2.33) for naproxen, and 1.58 (1.07-2.17) for rofecoxib 40. Concomitant use of cardioprotective aspirin does not appear to reduce the risk of acute MI with NSAIDs 41. A subsequent analysis using data from the Quebec administrative health cohort confirmed that all five NSAIDs, including naproxen, are associated with increased risk of MI.…”
mentioning
confidence: 99%